Additional cocopeat and coconut water improves the seedling growth of robusta coffee - Anjarsari, Intan Ratna Dewi; Febiola, Anita; Ariyanti, Mira; Defri, Ifwarisan (Kultivasi, 2024)
Robusta coffee production can be sucessed by using high-quality seedlings that have good growth performance. One of several keys to success in seedling production is the choosing best planting medium and providing exogenous growth regulators. These include using cocopeat planting media and giving coconut water. This research aims to determine whether using cocopeat planting media and providing coconut water can increase the growth of robusta coffee seedlings. The experiment used a randomized complete group design with six treatments and four replications; each experimental unit consisted of three robusta coffee seedlings. The six tested treatments were control (topsoil 100%); cocopeat 50% + topsoil 50%; cocopeat 100%; topsoil 100% + coconut water 200 mL; cocopeat 50% + topsoil 50% + coconut water 200 mL; and cocopeat 100% + coconut water 200 mL. This study indicated that cocopeat and coconut water could increase the growth of robusta coffee seedlings. The composition of cocopeat 100% and the combination of topsoil 50% + cocopeat 50% had an improvement effect on the growth of robusta coffee seedlings.